Creative Economy in Bucharest - Zamfir, Leonard (Calitatea Vieții, 2018)
The study intends to map geographically the clustering capabilities of the main creative industries in Bucharest. From the multitude of definitions in the field, it was chosen to present an analysis of the geographical spread of the media, publishing and software industries in Bucharest at the level of 2014, using and processing a database obtained during the analyzed period from the National Institute of Statistics (www.insse.ro). The present study analyzes the creative economy of DCMS using the values of three large economic indicators – CA (turnover), NrMs (Average Number of Employees and Number of Firms). These indicators are analyzed on the main areas of the macroeconomic creative economy (creative industries) as well as at micro level (geographic cardinal points – North, South, East, West, district, street, postal number). A vision that pursues quantitatively these areas (the most well-known and most accepted definition in this sense being the one given by the Department of Culture, Media and Sport of the United Kingdom – DCMS), a vision of the creative class developed by the American sociologist Richard Florida, and a part on urban development and planning, mainly by Charles Landry or Sharon Zukin. The creative economy is mainly related to urban development and may represent a new way of developing quality of life in large urban agglomerations. In the process of urban deindustrialisation, the creative economy is now seen as a social policy response to the deindustrialisation process; in other words, the poverty and stress caused by the closure of coal mines through the configuration of museums, which explains what kind of life has been in these coal mines, for example. Ideas are the core of the new economic system and represent a new alternative to the old economic problems: aging population and limited economic resources.